PERSEPSI KEBERFUNGSIAN KELUARGA BAGI ANAK DARI KELUARGA SINGLE PARENT - Rawdhah Binti Yasa; Fatmawati Fatmawati (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
Non-intact families have a negative influence on children's development. A child needs a warm and loving family atmosphere. In families that are not intact, this need is not satisfactorily obtained. The child cared for by a single mother loses a father figure, whereas the child cared for by a single father will lose a mother figure. From that explanation, the researchers were interested in examining more deeply about family functioning among children from single parent families in Bener Meriah District. Data collection was carried out using Family Functioning Scale developed by Moos and Moos (2002). The results showed that most subjects had a perception of medium family functioning category. This is supported by previous research, indicated that other family members also play a role in the formation of family functioning, even though one parent in the family does not exist.